Positive electrode and solid-state battery

By adopting a double-layer structure and ion-conducting material coating in the positive electrode active material layer of the solid battery, the problem of insufficient battery capacity and ion conductivity in the prior art is solved, and higher battery capacity and rate characteristics are achieved.

CN120359619APending Publication Date: 2025-07-22MURATA MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380089095.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-16
Filing Date
2023-12-07
Publication Date
2025-07-22

AI Technical Summary

Technical Problem

Existing solid batteries have shortcomings in improving performance, especially in improving battery capacity and ion conductivity.

Method used

A two-layer structure of a positive electrode active material layer is adopted, wherein the volume ratio of the first positive electrode active material region to the solid electrolyte is more than 6:4 and less than 8:2. The median diameter of the second positive electrode active material particles is greater than the median diameter of the first positive electrode active material particles, and an ion conductive material coating is provided at the interface to form a good ion conductive path.

Benefits of technology

Without damaging the energy density, the rate characteristics and battery capacity of the solid battery are improved, achieving better performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120359619A_ABST
    Figure CN120359619A_ABST
Patent Text Reader

Abstract

Provided is a positive electrode for a solid-state battery having more excellent performance. The positive electrode includes a positive electrode current collector and a positive electrode active material layer provided on the positive electrode current collector. The positive electrode active material layer has: a first positive electrode active material region that is provided in the positive electrode current collector and contains a plurality of first positive electrode active material particles to which a solid electrolyte is adhered; and a second positive electrode active material region that is provided on the opposite side from the positive electrode current collector when viewed from the first positive electrode active material region, and that contains a plurality of second positive electrode active material particles to which a solid electrolyte is adhered. The volume ratio of the plurality of first positive electrode active material particles to the solid electrolyte in the first positive electrode active material region is within the range of 6: 4 or more and 8: 2 or less. The median diameter of the plurality of second positive electrode active material particles is larger than the median diameter of the plurality of first positive electrode active material particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present technology relates to a positive electrode having a solid electrolyte and a solid battery including the positive electrode. Background Art

[0002] A variety of electronic devices such as mobile phones are becoming widespread, and thus, development of secondary batteries is underway as a power source that is small, lightweight, and capable of achieving a high energy density. The secondary battery includes a positive electrode, a negative electrode, and an electrolyte housed inside a packaging member.

[0003] In recent years, solid batteries as secondary batteries having a solid electrolyte instead of a liquid or gel electrolyte containing an organic solvent or the like have been developed (see, for example, Patent Documents 1 and 2).

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2017-157529

[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 2014-238925 Summary of the Invention

[0008] As described in the above prior art documents, various studies have been conducted to improve the performance of solid batteries. However, there is room for improvement in the performance of solid batteries.

[0009] The present technology has been made in view of the above problems, and an object thereof is to provide a solid battery having more excellent performance and a positive electrode for the solid battery.

[0010] The positive electrode according to one embodiment of the present disclosure includes a positive electrode current collector and a positive electrode active material layer provided on the positive electrode current collector. The positive electrode active material layer has: a first positive electrode active material region provided on the positive electrode current collector and including a plurality of first positive electrode active material particles to which a solid electrolyte (SE) is attached; and a second positive electrode active material region provided on the side opposite to the positive electrode current collector when viewed from the first positive electrode active material region and including a plurality of second positive electrode active material particles to which a solid electrolyte is attached. The volume ratio of the plurality of first positive electrode active material particles to the solid electrolyte in the first positive electrode active material region is in the range of 6:4 or more and 8:2 or less. The median diameter of the plurality of second positive electrode active material particles is larger than the median diameter of the plurality of first positive electrode active material particles.

[0011] In a solid-state battery using a positive electrode according to an embodiment of the present disclosure, the volume ratio of a plurality of first positive electrode active material particles to a solid electrolyte in a first positive electrode active material region relatively closer to the positive electrode current collector than a second positive electrode active material region is in a range of 6:4 or more and 8:2 or less. Moreover, the median diameter of the plurality of first positive electrode active material particles is smaller than the median diameter of the plurality of second positive electrode active material particles. Therefore, more solid electrolyte exists around the plurality of first positive electrode active material particles. Therefore, a good ion conduction path can be formed, and more excellent performance such as an improvement in rate characteristics can be achieved without sacrificing the energy density.

[0012] It should be noted that the effects of the present disclosure are not necessarily limited to the effects described herein, and may be any of a series of effects associated with the present disclosure described later. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 FIG. is a cross-sectional schematic view showing a structural example of a solid-state battery as an embodiment of the present disclosure.

[0014] Figure 2 FIG. is a cross-sectional schematic view showing a structural example of a positive electrode of the solid-state battery applied Figure 1 as shown. DETAILED DESCRIPTION

[0015] Hereinafter, an embodiment of the present disclosure will be described in detail with reference to the drawings. It should be noted that the order of description is as follows.

[0016] 0. Summary of the Present Disclosure

[0017] 1. One Embodiment

[0018] 1.1 Structure of the Solid-State Battery

[0019] 1.2 Manufacturing Method of the Solid-State Battery

[0020] 1.3 Operation and Effects of the Solid-State Battery

[0021] 2. Examples

[0022] It should be noted that the "solid-state battery" of the present disclosure refers to a battery whose constituent elements are solid. For example, the "solid-state battery" of the present disclosure is a laminated solid-state battery formed by laminating multiple layers. The multiple layers are formed of a sintered body, for example. The "solid-state battery" of the present disclosure includes not only a secondary battery capable of repeated charge and discharge but also a primary battery capable of only discharging.

[0023] [0. Summary of the Present Disclosure]

[0024] First, the summary of the present disclosure will be described.

[0025] Various studies have been conducted on improving the performance of solid-state batteries. Since solid-state batteries have a solid electrolyte, generally speaking, compared with batteries using a liquid electrolyte, solid-state batteries have excellent high-temperature resistance and high safety.

[0026] In addition, in the above-mentioned Patent Document 1, a positive electrode active material layer having a structure in which a first active material layer and a second active material layer having different porosity rates are sequentially laminated from the current collector side is proposed. Specifically, the porosity rate of the first active material layer is set to 0% or more and less than 10%, and the porosity rate of the second active material layer is set to 10% or more and less than 60%, so that the precursor solution of the solid electrolyte is easily impregnated into the positive electrode active material layer during manufacturing. However, in an electrode having such a positive electrode active material layer, since the porosity rate of the second active material layer is 10% or more and less than 60%, the energy density is reduced and the battery capacity may be reduced. In addition, since the average particle diameter of the particulate positive electrode active material constituting the first active material layer is set to 100 nm or more and less than 5 μm, when a coating film of an ion-conductive material is formed on the surface of the particulate positive electrode active material, the volume occupancy rate of the positive electrode active material is relatively reduced, and thus the battery capacity may be reduced.

[0027] In addition, in the above-mentioned Patent Document 2, for example, as Figure 1 shown, the volume ratio of the positive electrode active material in the second positive electrode active material layer 12b on the solid electrolyte layer 40 side to the solid electrolyte material is made smaller than the volume ratio of the positive electrode active material in the first positive electrode active material layer 12a on the positive electrode current collector 11 side to the solid electrolyte material. The purpose is to increase the solid electrolyte material on the solid electrolyte layer side and form a relatively thick Li ion conduction path to improve the rate characteristics. However, in the invention of Patent Document 2, since the amount of the positive electrode active material in the second positive electrode active material layer 12b is reduced, it is considered that the reduction of the battery capacity still cannot be avoided.

[0028] In view of the above situation, the present applicant proposes a positive electrode that can obtain higher ion conductivity while suppressing the reduction of battery capacity, and a solid-state battery using the positive electrode.

[0029] [1. One embodiment]

[0030] <1.1 Structure of the solid-state battery>

[0031] Refer to Figure 1 and Figure 2 , and the structure of the solid-state battery 100 as one embodiment of the present disclosure will be described. Figure 1It is a schematic cross-sectional view schematically showing the structure of the solid-state battery 100. The solid-state battery 100 has a stacked structure in which a positive electrode 10, a solid electrolyte layer 20, and a negative electrode 30 are stacked in this order. The negative electrode 30 has a negative electrode current collector 31 and a negative electrode active material layer 32. The solid-state battery 100 may also have a structure in which units formed by stacking the positive electrode 10, the solid electrolyte layer 20, the negative electrode 30, and the solid electrolyte layer 20 in this order are repeated and stacked multiple times.

[0032] (Positive Electrode 10)

[0033] Figure 2 It is a cross-sectional schematic diagram showing an enlarged view of the positive electrode 10 and a part of the solid electrolyte layer 20 in the solid-state battery 100. The positive electrode 10 is an electrode layer containing at least a positive electrode active material. The positive electrode 10 has a positive electrode current collector 11 and a positive electrode active material layer 12.

[0034] The positive electrode current collector 11 is, for example, a metal foil. As the constituent material of the positive electrode current collector 11, one metal (single metal) selected from the group consisting of Al (aluminum), Cu (copper), Mg (magnesium), Ti (titanium), Fe (iron), Co (cobalt), Ni (nickel), Zn (zinc), Ge (germanium), In (indium), Au (gold), Pt (platinum), Ag (silver), and Pd (palladium) or an alloy containing two or more metal elements selected from the above group can be cited. In addition, the positive electrode current collector 11 may also be a sintered body. This is to be able to form the solid-state battery 100 by integral firing or to reduce the internal resistance of the positive electrode current collector 11. When the positive electrode current collector 11 is a sintered body, the positive electrode current collector 11 may also contain a conductive aid and a sintering aid. The conductive aid contained in the positive electrode current collector 11 may be, for example, the same type of conductive aid as the conductive aid contained in the positive electrode active material layer 12. In addition, the sintering aid contained in the positive electrode current collector 11 may be, for example, the same type of sintering aid as the sintering aid contained in the positive electrode active material layer 12.

[0035] The shape of the positive electrode current collector 11 can be, for example, plate-like, foil-like, or mesh-like, etc. The surface of the positive electrode current collector 11 may be smooth or may have irregularities.

[0036] (Positive Electrode Active Material Layer 12)

[0037] The positive electrode active material layer 12 contains a positive electrode active material as a main component. The positive electrode active material contained in the positive electrode active material layer 12 is a material that participates in the insertion and extraction of ions in the solid battery 100 and participates in the transfer of electrons to and from the external circuit. Ions move between the positive electrode 10 and the negative electrode 30 via the solid electrolyte (i.e., ion conduction). The insertion and extraction of ions into and from the positive electrode active material is accompanied by the oxidation or reduction of the positive electrode active material. Charging and discharging are performed by transferring electrons or holes for such redox reactions to the positive electrode 10 or the negative electrode 30. The positive electrode active material layer 12 is, for example, a layer capable of inserting and extracting lithium ions, sodium ions, protons (H + ), potassium ions (K + ), magnesium ions (Mg 2+ ), aluminum ions (Al 3+ ), silver ions (Ag + ), fluoride ions (F - ), or chloride ions (Cl - ). That is, the solid battery 100 is an all-solid-state secondary battery in which the above-mentioned ions move between the positive electrode 10 and the negative electrode 30 via the solid electrolyte to perform charging and discharging.

[0038] (Positive electrode active material)

[0039] Examples of the positive electrode active material contained in the positive electrode 10 include at least one selected from the group consisting of lithium-containing phosphate compounds having a NASICON-type structure, lithium-containing phosphate compounds having an olivine-type structure, lithium-containing layered oxides, and lithium-containing oxides having a spinel-type structure. As an example of a lithium-containing phosphate compound having a NASICON-type structure, Li3V2(PO4)3 etc. can be cited. As an example of a lithium-containing phosphate compound having an olivine-type structure, Li3Fe2(PO4)3, LiFePO4, LiMnPO4, LiFe 0.6 Mn 0.4 PO4 etc. can be cited. As an example of a lithium-containing layered oxide, LiCoO2, LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, LiCo 0.8 Ni 0.15 Al 0.05 O2 etc. can be cited. As an example of a lithium-containing oxide having a spinel-type structure, LiMn2O4, LiNi 0.5 Mn 1.5 O4 etc. can be cited.

[0040] In addition, as the positive electrode active material capable of inserting and extracting sodium ions, at least one selected from the group consisting of sodium-containing phosphate compounds having a NASICON-type structure, sodium-containing phosphate compounds having an olivine-type structure, sodium-containing layered oxides, and sodium-containing oxides having a spinel-type structure can be cited.

[0041] As Figure 2 shown, the positive electrode active material layer 12 has a laminated structure in which a first positive electrode active material region L1 and a second positive electrode active material region L2 are laminated in sequence on the positive electrode current collector 11.

[0042] The first positive electrode active material region L1 is provided on the positive electrode current collector 11 and is a porous molded body including a plurality of first positive electrode active material particles 1 to which a solid electrolyte SE is attached. The first positive electrode active material particles 1 are particles including the above-mentioned positive electrode active material. The solid electrolyte SE exists around the plurality of first positive electrode active material particles 1. The solid electrolyte SE also exists in the gaps between the plurality of first positive electrode active material particles 1. In addition, a plurality of voids exist in the solid electrolyte SE in the first positive electrode active material region L1. The solid electrolyte SE will be described in detail later. In addition, the volume ratio of the plurality of first positive electrode active material particles 1 to the solid electrolyte SE in the first positive electrode active material region L1 may be in the range of 6:4 or more and 8:2 or less.

[0043] The second positive electrode active material region L2 is provided on the side opposite to the positive electrode current collector 11 when viewed from the first positive electrode active material region L1. The second positive electrode active material region L2 is a porous molded body including a plurality of second positive electrode active material particles 2 to which a solid electrolyte SE is attached. The second positive electrode active material particles 2 are particles including the above-mentioned positive electrode active material. The positive electrode active material constituting the second positive electrode active material particles 2 may be the same as or different from the positive electrode active material constituting the first positive electrode active material particles 1. The solid electrolyte SE exists around the plurality of second positive electrode active material particles 2. The solid electrolyte SE also exists in the gaps between the plurality of second positive electrode active material particles 2. In addition, a plurality of voids also exist in the solid electrolyte SE in the second positive electrode active material region L2. In addition, the volume ratio of the plurality of second positive electrode active material particles 2 to the solid electrolyte SE in the second positive electrode active material region L2 may also be in the range of 6:4 or more and 8:2 or less.

[0044] The positive electrode active material layer 12 of the present embodiment is not limited to a manner in which the boundary between the first positive electrode active material region L1 and the second positive electrode active material region L2 is clear in the stacked cross section, and may also have a manner in which the boundary between the first positive electrode active material region L1 and the second positive electrode active material region L2 is not clear in the stacked cross section. In addition, the thickness of the first positive electrode active material region L1 and the thickness of the second positive electrode active material region L2 may be substantially the same or different.

[0045] It should be noted that the volume ratio of the plurality of first positive electrode active material particles 1 in the first positive electrode active material region L1 to the solid electrolyte SE can be obtained, for example, from an image of an arbitrary cross section of the first positive electrode active material region L1 along the stacking direction, by separately calculating the sum of the cross-sectional areas of the plurality of first positive electrode active material particles 1 present in a unit region (for example, Figure 2 the region R1 enclosed by the single dotted line in the figure) and the sum of the cross-sectional areas of the solid electrolyte SE present in the unit region (region R1).

[0046] The volume ratio of the plurality of second positive electrode active material particles 2 in the second positive electrode active material region L2 to the solid electrolyte SE can be obtained, for example, from an image of an arbitrary cross section of the second positive electrode active material region L2 along the stacking direction, by separately calculating the sum of the cross-sectional areas of the plurality of second positive electrode active material particles 2 present in a unit region (for example, Figure 2 the region R2 enclosed by the single dotted line in the figure) and the sum of the cross-sectional areas of the solid electrolyte SE present in the unit region (region R2).

[0047] It should be noted that the filling rate F of the positive electrode active material layer 12 can be, for example, 85% or more. The filling rate F here refers to the volume occupancy rate of the first positive electrode active material particles 1, the second positive electrode active material particles 2, and the solid electrolyte SE present in the positive electrode active material layer 12, and is the volume ratio of the part other than the voids in the positive electrode active material layer 12. The filling rate F can be obtained, for example, by taking an image of an arbitrary cross section of the positive electrode active material layer 12 using a scanning electron microscope (SEM) and calculating it using image processing software. Specifically, for example, using the public domain ImageJ as the image processing software, from an arbitrary cross section image (SEM image) of the positive electrode active material layer 12, the overall area of the SEM image is obtained using "Set Measurement". Then, the contrast part corresponding to the voids is determined using "Threshold". The area of the "contrast part corresponding to the voids" is obtained using "Limit to Threshold" of "Set Measurement". The filling rate F is obtained as {(the overall area of the SEM image) - (the area of the contrast part corresponding to the voids)} / (the overall area of the SEM image) × 100 (%).

[0048] In the positive electrode active material layer 12 of the present embodiment, the median diameter of the plurality of second positive electrode active material particles 2 is larger than the median diameter of the plurality of first positive electrode active material particles 1. The median diameter of the plurality of first positive electrode active material particles 1 is, for example, larger than 1 μm and smaller than 20 μm. The median diameter of the plurality of second positive electrode active material particles is, for example, larger than 1 μm and smaller than 20 μm.

[0049] Alternatively, on at least a part of the interface between the first positive electrode active material particles 1 and the solid electrolyte SE and at least a part of the interface between the second positive electrode active material particles 2 and the solid electrolyte SE, there is a coating film containing an ion conductive material. The thickness of the coating film is, for example, 1 nm or more and 100 nm or less. The ion conductive material mentioned here is, for example, a compound represented by LiXY. Here, X is at least one element selected from the group consisting of B (boron), Al (aluminum), Si (silicon), P (phosphorus), Ti (titanium), Ge (germanium), Zr (zirconium), Nb (niobium), In (indium), Sn (tin), Hf (hafnium), Ta (tantalum), and W (tungsten), and Y is at least one element selected from the group consisting of O (oxygen), S (sulfur), F (fluorine), Cl (chlorine), Br (bromine), and I (iodine). The ion conductive material constituting the coating film is, for example, LiNbO3.

[0050] (Solid electrolyte layer 20 and solid electrolyte SE)

[0051] The solid electrolyte layer 20 has the solid electrolyte SE. The solid electrolyte SE exists not only in the solid electrolyte layer 20 but also in each of the first positive electrode active material region L1 and the second positive electrode active material region L2 in the positive electrode active material layer 12. In addition, a part of the solid electrolyte SE contacts the positive electrode current collector 11 near the interface between the first positive electrode active material region L1 and the positive electrode current collector 11.

[0052] The solid electrolyte SE is, for example, a material capable of conducting ions such as lithium ions or sodium ions. In particular, the solid electrolyte constituting the battery structural unit in a solid battery forms a solid electrolyte layer 20 capable of conducting lithium ions, for example, between the positive electrode 10 and the negative electrode 30. As specific solid electrolytes, for example, a lithium-containing phosphate compound having a NASICON-type structure, an oxide having a perovskite-type structure, an oxide having a garnet-type or garnet-like structure, etc. can be cited. As the lithium-containing phosphate compound having a NASICON-type structure, LixMy(PO4)3 (1 ≤ x ≤ 2, 1 ≤ y ≤ 2, M is at least one selected from the group consisting of Ti, Ge, Al, Ga, and Zr) can be cited. As an example of the lithium-containing phosphate compound having a NASICON-type structure, for example, Li 1.2 Al 0.2 Ti1.8 (PO4)3, etc. As an example of an oxide having a perovskite structure, La 0.55 Li 0.35 TiO3, etc. As an example of an oxide having a garnet or garnet-like structure, Li7La3Zr2O 12 , etc. In addition, as a solid electrolyte capable of conducting sodium ions, for example, a sodium-containing phosphate compound having a NASICON structure, an oxide having a perovskite structure, an oxide having a garnet or garnet-like structure, etc. can be cited. As a sodium-containing phosphate compound having a NASICON structure, NaxMy(PO4)3 (1 ≤ x ≤ 2, 1 ≤ y ≤ 2, M is at least one selected from the group consisting of Ti, Ge, Al, Ga, and Zr) can be cited.

[0053] The solid electrolyte layer 20 may also contain a sintering aid. The sintering aid that can be contained in the solid electrolyte layer 20 can be selected, for example, from the same materials as the sintering aids that can be contained in the positive electrode 10 and the negative electrode 30.

[0054] (Negative electrode 30)

[0055] The negative electrode 30 is an electrode layer containing at least a negative electrode active material. The negative electrode 30 has a negative electrode current collector 31 and a negative electrode active material layer 32. The negative electrode current collector 31 is, for example, a metal foil such as a copper foil. In addition, the negative electrode current collector 31 may also be a sintered body. This is for the purpose of being able to form the solid battery 100 by integral firing, or for the purpose of reducing the internal resistance of the negative electrode current collector. When the negative electrode current collector is a sintered body, the negative electrode current collector may also contain a conductive aid and a sintering aid.

[0056] (Negative electrode active material)

[0057] The negative electrode active material contained in the negative electrode 30 is the same as the positive electrode active material contained in the positive electrode 10, and is a material that participates in the insertion and extraction of ions in the solid battery 100 and participates in the transfer of electrons with the external circuit. Ions move between the positive electrode 10 and the negative electrode 30 via the solid electrolyte layer 20 (i.e., ion conduction). The insertion and extraction of ions into and from the negative electrode active material are accompanied by the oxidation or reduction of the negative electrode active material. The electrons or holes used for such redox reactions are transferred to the positive electrode 10 or the negative electrode 30, thereby performing charge and discharge. The negative electrode active material can, for example, insert and extract lithium ions, sodium ions, protons (H + ), potassium ions (K + ), magnesium ions (Mg 2+ ), aluminum ions (Al 3+ ), silver ions (Ag + ), fluoride ions (F - ) or chloride ions (Cl- ). As the negative electrode active material contained in the negative electrode 30, for example, at least one selected from the group consisting of oxides, graphite-lithium compounds, lithium alloys, lithium-containing phosphate compounds having a NASICON structure, lithium-containing phosphate compounds having an olivine structure, and lithium-containing oxides having a spinel structure can be cited. The oxide contains at least one element selected from the group consisting of Ti, Si, Sn, Cr, Fe, Nb, and Mo. As an example of the lithium alloy, Li-Al etc. can be cited. As an example of the lithium-containing phosphate compound having a NASICON structure, Li3V2(PO4)3, LiTi2(PO4)3 etc. can be cited. As an example of the lithium-containing phosphate compound having an olivine structure, Li3Fe2(PO4)3, LiCuPO4 etc. can be cited. As an example of the lithium-containing oxide having a spinel structure, Li4Ti5O 12 etc.

[0058] In addition, as the negative electrode active material capable of intercalating and deintercalating sodium ions, at least one selected from the group consisting of sodium-containing phosphate compounds having a NASICON structure, sodium-containing phosphate compounds having an olivine structure, and sodium-containing oxides having a spinel structure can be cited.

[0059] <1.2 Method for manufacturing the solid battery 100>

[0060] An example of the method for manufacturing the solid battery 100 will be described. When manufacturing the solid battery 100, printing methods such as screen printing, a green sheet method using green sheets, or a composite method thereof can be used. Hereinafter, an example of the manufacturing method will be described, but the present disclosure is not limited to the following manufacturing method. In addition, the chronological matters such as the following description order are only for convenience of explanation, and the present disclosure is not limited to this matter.

[0061] First, the positive electrode 10 is fabricated. Specifically, after preparing a plurality of first positive electrode active material particles 1 having a specified median diameter, a LiNbO3-based ionic conduction material is coated on the plurality of first positive electrode active material particles 1 using a rolling flow coating apparatus. Subsequently, the plurality of first positive electrode active material particles 1 coated with the ionic conduction material and the solid electrolyte SE are kneaded at a specified volume ratio (e.g., 6:4), thereby fabricating a first positive electrode active material mixture. Similarly, after preparing a plurality of second positive electrode active material particles 2 having a specified median diameter, a LiNbO3-based ionic conduction material is coated on the plurality of second positive electrode active material particles 2 using a rolling flow coating apparatus. Then, the plurality of second positive electrode active material particles 2 coated with the ionic conduction material and the solid electrolyte SE are kneaded at a specified volume ratio (e.g., 6:4), thereby fabricating a second positive electrode active material mixture. Next, a positive electrode current collector 11 is prepared, and the above-described first positive electrode active material mixture is coated on the surface of the positive electrode current collector 11, thereby fabricating a first positive electrode active material region L1. Further, the above-described second positive electrode active material mixture is coated on the first positive electrode active material region L1, thereby fabricating a second positive electrode active material region L2. In addition, a laminate in which the first positive electrode active material region L1 and the second positive electrode active material region L2 are sequentially laminated on the positive electrode current collector 11 is compression-molded using a press, thereby forming a positive electrode active material layer 12. The positive electrode 10 is obtained through the above operations.

[0062] Next, the negative electrode 30 is fabricated. Specifically, a negative electrode active material mixture is fabricated by kneading a plurality of negative electrode active material particles and the solid electrolyte SE at a specified volume ratio (e.g., 6:4). Subsequently, a negative electrode current collector 31 is prepared, and the above-described negative electrode active material mixture is coated on the surface of the negative electrode current collector 31. Then, the negative electrode active material mixture coated on the negative electrode current collector 31 is compression-molded using a press, thereby forming a negative electrode active material layer 32 on the negative electrode current collector 31. The negative electrode 30 is obtained through the above operations.

[0063] Finally, the positive electrode 10, the solid electrolyte layer 20, and the negative electrode 30 are sequentially laminated to fabricate a laminate, and then the laminate is compressed using a press, thereby enabling the fabrication of the solid-state battery 100.

[0064] <1.3 Function and Effect of the Solid-State Battery>

[0065] Generally, as important characteristics required for a solid-state battery, volumetric energy density, high-rate charge / discharge characteristics, durability, etc. can be cited. These characteristics are, in most cases, determined by the positive electrode in the solid-state battery. As general measures for increasing the volumetric energy density, measures such as expanding the particle size distribution or using a positive electrode active material having a bimodal particle size distribution to increase the geometric packing density can be cited. In addition, in order to achieve an improvement in high-rate charge / discharge characteristics, generally, a measure of using smaller-sized positive electrode active material particles to increase the reaction surface area is known. However, simply reducing the particle size of the positive electrode active material particles will reduce the packing density of the positive electrode active material particles in the positive electrode active material layer. In addition, in order to suppress the reaction between the positive electrode active material particles and the solid electrolyte and improve the durability of the positive electrode active material particles, it is desirable to provide a coating film composed of an ion-conductive material at the interface between the positive electrode active material particles and the solid electrolyte. However, since the coating film requires a certain thickness, as the particle size of the positive electrode active material particles becomes smaller, the volume occupied by the coating film in the positive electrode active material layer becomes higher relative to the volume of the positive electrode active material particles. Therefore, reducing the particle size of the positive electrode active material particles also causes a secondary technical problem of reducing the energy density per unit volume of the active material.

[0066] In the solid-state battery 100 of the present embodiment, the positive electrode active material layer 12 has a first positive electrode active material region L1 and a second positive electrode active material region L2 laminated in order from the positive electrode current collector 11 side. Here, the volume ratio of the plurality of first positive electrode active material particles 1 to the solid electrolyte SE in the first positive electrode active material region L1 is in the range of 6:4 or more and 8:2 or less. Moreover, the median diameter of the plurality of first positive electrode active material particles 1 is smaller than the median diameter of the plurality of second positive electrode active material particles 2. Therefore, more solid electrolyte SE exists around the plurality of first positive electrode active material particles 1. Therefore, in the solid-state battery 100 including the positive electrode 10, a good ion conduction path can be formed, the rate characteristics can be improved without impairing the energy density, and more excellent performance can be achieved.

[0067] In the solid-state battery 100 of the present embodiment, since a coating film containing an ion-conductive material such as LiNbO3 exists on at least a part of the interface between the first positive electrode active material particles 1 and the solid electrolyte SE and at least a part of the interface between the second positive electrode active material particles 2 and the solid electrolyte SE, a better ion conduction path can be formed and more excellent performance can be achieved.

[0068] In addition, in the solid-state battery 100 of the present embodiment, a part of the solid electrolyte SE contacts the positive electrode current collector 11 near the interface between the first positive electrode active material region L1 and the positive electrode current collector 11. Therefore, the solid-state battery 100 can form a better ion conduction path and can achieve more excellent performance.

[0069] [2. Examples]

[0070] Examples of the present disclosure will be described.

[0071] <Example 1>

[0072] As described below, a solid-state battery (half-cell) for evaluation was fabricated, and then its battery characteristics were evaluated. The solid-state battery includes Figure 1 the positive electrode (evaluation electrode) of the present disclosure shown in the figure, a reference electrode as its counter electrode, and a solid electrolyte layer provided between the positive electrode and the reference electrode. In addition, an indium-lithium alloy foil was used as the reference electrode.

[0073] (Fabrication of positive electrode)

[0074] First, an Al (aluminum) foil was prepared as the positive electrode current collector. Next, as a plurality of first positive electrode active material particles, Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 with a median diameter D50(1) of 5.0 μm was prepared. On these plurality of first positive electrode active material particles, LiNbO3 as an ion conduction material was coated with a target thickness of 5 nm using a rolling flow coating device ("MP-01" manufactured by Powrex Corporation). Then, the plurality of first positive electrode active material particles coated with LiNbO3 were kneaded with Li6PS5Cl as a solid electrolyte at a volume ratio of 6:4 to produce a first positive electrode active material mixture. Next, as a plurality of second positive electrode active material particles, Li(Ni 0.5 Co 0.2 Mn 0.3)O2. On these multiple second positive electrode active material particles, LiNbO3, which is an ion-conducting material, was coated with a target thickness of 5 nm using a rolling flow coating device ("MP-01" manufactured by Powrex Corporation). Then, the multiple second positive electrode active material particles coated with LiNbO3 were kneaded with Li6PS5Cl, which is a solid electrolyte, at a volume ratio of 6:4 to produce a second positive electrode active material mixture. Next, the above-mentioned first positive electrode active material mixture was coated on the surface of the positive electrode current collector to produce a first positive electrode active material region, and then a second positive electrode active material region was produced by coating the above-mentioned second positive electrode active material mixture on this first positive electrode active material region. Then, a press was used to press-mold a laminate in which the first positive electrode active material region and the second positive electrode active material region were sequentially laminated on the positive electrode current collector at a pressure of 98 MPa, thereby forming a positive electrode active material layer and obtaining a positive electrode. It should be noted that in this embodiment, the thickness of the positive electrode active material region and the thickness of the positive electrode active material region were each set to 30 μm.

[0075] (Fabrication of a solid-state battery (half-cell))

[0076] After attaching a solid electrolyte layer (also called a separator) made of the solid electrolyte Li6PS5Cl to the positive electrode obtained as described above, press-molding was sequentially performed at 98 MPa and 588 MPa using a press to form a laminate of the positive electrode and the solid electrolyte layer. In addition, on the side opposite to the positive electrode when viewed from the solid electrolyte layer, an indium-lithium alloy foil was attached as the negative electrode to obtain a solid-state battery (half-cell).

[0077] (Evaluation of battery characteristics)

[0078] The battery characteristics of the fabricated solid-state battery of Example 1 were evaluated, and the results shown in Table 1 were obtained. Here, at room temperature, the charge capacity [mAh / g] when charging the solid-state battery of Example 1 at a 2C rate was measured. It should be noted that 1C is the magnitude of the current that fully charges (or discharges) the theoretical capacity of the battery in 1 hour during constant current charge and discharge. In addition, the solid-state battery of Example 1 was cut along the stacking direction to expose the cross-section along the stacking direction, and an image of this cross-section was obtained by a scanning electron microscope (SEM). By analyzing the image of this cross-section, the filling rates of the multiple first positive electrode active material particles and the multiple second positive electrode active material particles in the entire positive electrode active material layer were measured.

[0079] [Table 1]

[0080]

[0081] <Example 2>

[0082] As shown in Table 1, except that Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 with a median diameter D50(1) of 2.0 μm was used as a plurality of first positive electrode active material particles, and Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 with a median diameter D50(2) of 5.0 μm was used as a plurality of second positive electrode active material particles, a solid battery of Example 2 was fabricated in the same manner as in Example 1. Then, the battery characteristics of the solid battery of Example 2 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0083] <Example 3>

[0084] As shown in Table 1, except that Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 with a median diameter D50(1) of 2.0 μm was used as a plurality of first positive electrode active material particles, a solid battery of Example 3 was fabricated in the same manner as in Example 1. Then, the battery characteristics of the solid battery of Example 3 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0085] <Example 4>

[0086] As shown in Table 1, except that the volume ratio of a plurality of first positive electrode active material particles to Li6PS5Cl as a solid electrolyte and the volume ratio of a plurality of second positive electrode active material particles to Li6PS5Cl as a solid electrolyte were both 7:3, a solid battery of Example 4 was fabricated in the same manner as in Example 1. Then, the battery characteristics of the solid battery of Example 4 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0087] <Example 5>

[0088] Except that LiNbO3 was not coated on each of a plurality of first positive electrode active material particles and a plurality of second positive electrode active material particles, a solid battery of Example 5 was fabricated in the same manner as in Example 2. Then, the battery characteristics of the solid battery of Example 5 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0089] <Comparative Example 1>

[0090] As shown in Table 1, except that Li(Ni 0.5 Co 0.2 Mn 0.3)Except for using O2 as a plurality of first positive electrode active material particles and a plurality of second positive electrode active material particles, a solid battery of Comparative Example 1 was fabricated in the same manner as in Example 1. Then, the battery characteristics of the solid battery of Comparative Example 1 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0091] <Comparative Example 2>

[0092] As shown in Table 1, except for using Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 with a median diameter D50(1) of 10.0 μm as a plurality of first positive electrode active material particles and using Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 with a median diameter D50(2) of 5.0 μm as a plurality of second positive electrode active material particles, a solid battery of Comparative Example 2 was fabricated in the same manner as in Example 1. Then, the battery characteristics of the solid battery of Comparative Example 2 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0093] <Comparative Example 3>

[0094] As shown in Table 1, except for using Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 with median diameters D50(1) and (2) of 3.5 μm as a plurality of first positive electrode active material particles and a plurality of second positive electrode active material particles, a solid battery of Comparative Example 3 was fabricated in the same manner as in Example 1. Then, the battery characteristics of the solid battery of Comparative Example 3 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0095] <Comparative Example 4>

[0096] As shown in Table 1, except for using Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 with a median diameter D50(1) of 2.0 μm as a plurality of second positive electrode active material particles, a solid battery of Comparative Example 4 was fabricated in the same manner as in Example 1. Then, the battery characteristics of the solid battery of Comparative Example 4 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0097] <Comparative Example 5>

[0098] As shown in Table 1, except for using Li(Ni 0.5 Co 0.2 Mn 0.3)In addition to O2 as a plurality of first positive electrode active material particles and a plurality of second positive electrode active material particles, a solid battery of Comparative Example 5 was fabricated in the same manner as in Example 1. Then, the battery characteristics of the solid battery of Comparative Example 5 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0099] <Comparative Example 6>

[0100] As shown in Table 1, except that Li(Ni 0.5 Co 0.2 Mn 0.3 )O2 with a median diameter D50 (1), (2) of 2.0 μm was used as a plurality of first positive electrode active material particles and a plurality of second positive electrode active material particles, a solid battery of Comparative Example 7 was fabricated in the same manner as in Example 1. Then, the battery characteristics of the solid battery of Comparative Example 7 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0101] <Comparative Example 7>

[0102] A solid battery of Comparative Example 8 was fabricated in the same manner as in Comparative Example 4, except that LiNbO3 was not coated on each of the plurality of first positive electrode active material particles and the plurality of second positive electrode active material particles. Then, the battery characteristics of the solid battery of Comparative Example 8 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0103] <Comparative Example 8>

[0104] As shown in Table 1, a solid battery of Comparative Example 9 was fabricated in the same manner as in Comparative Example 2, except that the volume ratio of the plurality of first positive electrode active material particles to Li6PS5Cl as the solid electrolyte and the volume ratio of the plurality of second positive electrode active material particles to Li6PS5Cl as the solid electrolyte were both 7:3. Then, the battery characteristics of the solid battery of Comparative Example 9 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0105] <Comparative Example 9>

[0106] As shown in Table 1, a solid battery of Comparative Example 10 was fabricated in the same manner as in Example 1, except that the volume ratio of the plurality of first positive electrode active material particles to Li6PS5Cl as the solid electrolyte and the volume ratio of the plurality of second positive electrode active material particles to Li6PS5Cl as the solid electrolyte were both 5:5. Then, the battery characteristics of the solid battery of Comparative Example 10 were evaluated in the same manner as in Example 1. The results are shown together in Table 1.

[0107] [Investigation]

[0108] As shown in Table 1, in Examples 1 to 4, compared with Comparative Examples 1 to 9, both high charge capacity and high volumetric energy density are achieved. It is considered that this is because in Examples 1 to 4, the volume ratio of the first positive electrode active material particles to the solid electrolyte is 6:4 or 7:3, and the median diameter D50(2) of the plurality of second positive electrode active material particles is greater than the median diameter D50(1) of the plurality of first positive electrode active material particles. Therefore, a good ion conduction path is formed in the positive electrode active material layer, and the ion conductivity in the positive electrode can be improved.

[0109] In addition, Example 5 and Comparative Example 7 are different from Examples 1 to 4 and the like in that LiNbO3 is not coated on each of the first positive electrode active material particles and the second positive electrode active material particles. Thus, neither Example 5 nor Comparative Example 7 forms a coating film on each of the first positive electrode active material particles and the second positive electrode active material particles. However, from the comparison between the two, a clear difference is shown in both the charge capacity and the volumetric energy density. That is, in Example 5, higher values are shown in both the charge capacity and the volumetric energy density compared with Comparative Example 7. The reason is considered to be that in Example 5, since the volume ratio of the first positive electrode active material particles to the solid electrolyte is 6:4 or 7:3, and the median diameter D50(2) of the plurality of second positive electrode active material particles is greater than the median diameter D50(1) of the plurality of first positive electrode active material particles, a good ion conduction path is formed in the positive electrode active material layer, and the ion conductivity in the positive electrode can be improved.

[0110] As described above, several embodiments, modification examples, and examples of the present disclosure have been described. However, the structure of the present disclosure is not limited to the structures described above, and various modifications can be made.

[0111] Specifically, for example, in the above-described one embodiment, the case where the positive electrode active material layer 12 has a two-layer structure including the first positive electrode active material region L1 and the second positive electrode active material region L2 is illustrated. However, the solid-state battery of the present disclosure is not limited to this mode. For example, the positive electrode active material layer may have a multi-layer structure of three or more layers including positive electrode active material particles having different median diameters. In this case, the median diameter of the positive electrode active material particles in the positive electrode active material region closest to the positive electrode current collector may be smaller than the median diameter of the positive electrode active material particles in other positive electrode active material regions.

[0112] In addition, the effects described in this specification are merely examples, and the effects of the present disclosure are not limited to the effects described in this specification. Therefore, other effects can also be obtained for the present disclosure.

[0113] In addition, the present disclosure can take the following forms.

[0114] <1>A positive electrode, comprising:

[0115] a positive electrode current collector; and

[0116] a positive electrode active material layer provided on the positive electrode current collector,

[0117] the positive electrode active material layer having:

[0118] a first positive electrode active material region provided on the positive electrode current collector and including a plurality of first positive electrode active material particles to which a solid electrolyte is attached; and

[0119] a second positive electrode active material region provided on the side opposite to the positive electrode current collector with respect to the first positive electrode active material region and including a plurality of second positive electrode active material particles to which the solid electrolyte is attached,

[0120] a volume ratio of the plurality of first positive electrode active material particles to the solid electrolyte in the first positive electrode active material region is in a range of 6:4 or more and 8:2 or less,

[0121] a median diameter of the plurality of second positive electrode active material particles is larger than a median diameter of the plurality of first positive electrode active material particles.

[0122] <2>The positive electrode according to <1> above,

[0123] a volume ratio of the plurality of first positive electrode active material particles to the solid electrolyte in the second positive electrode active material region is in a range of 6:4 or more and 8:2 or less.

[0124] <3>The positive electrode according to <1> or <2> above,

[0125] on at least a part of an interface between the first positive electrode active material particles and the solid electrolyte and at least a part of an interface between the second positive electrode active material particles and the solid electrolyte, there is a coating film containing an ion conductive material.

[0126] <4>The positive electrode according to <3> above,

[0127] when at least one element selected from B (boron), Al (aluminum), Si (silicon), P (phosphorus), Ti (titanium), Ge (germanium), Zr (zirconium), Nb (niobium), In (indium), Sn (tin), Hf (hafnium), Ta (tantalum), and W (tungsten) is defined as X, and at least one element selected from O (oxygen), S (sulfur), F (fluorine), Cl (chlorine), Br (bromine), and I (iodine) is defined as Y, the coating film contains a compound represented by LiXY as the ion conductive material.

[0128] <5> The positive electrode according to <3> or <4> above,

[0129] The ion-conductive material is LiNbO3.

[0130] <6> The positive electrode according to any one of <1> to <5> above,

[0131] A part of the solid electrolyte is in contact with the positive electrode current collector.

[0132] <7>

[0133] A solid battery includes, in sequence, the positive electrode, the solid electrolyte layer, and the negative electrode according to any one of <1> to <6> above.

Claims

1. A positive electrode, comprising: A positive electrode current collector; and A positive electrode active material layer provided on the positive electrode current collector, The positive electrode active material layer having: A first positive electrode active material region provided on the positive electrode current collector and including a plurality of first positive electrode active material particles to which a solid electrolyte is attached; and A second positive electrode active material region provided on the side opposite to the positive electrode current collector with respect to the first positive electrode active material region and including a plurality of second positive electrode active material particles to which the solid electrolyte is attached, The volume ratio of the plurality of first positive electrode active material particles to the solid electrolyte in the first positive electrode active material region is in the range of 6:4 or more and 8:2 or less, The median diameter of the plurality of second positive electrode active material particles is larger than the median diameter of the plurality of first positive electrode active material particles.

2. The positive electrode according to claim 1, wherein The volume ratio of the plurality of first positive electrode active material particles to the solid electrolyte in the second positive electrode active material region is in the range of 6:4 or more and 8:2 or less.

3. The positive electrode according to claim 1 or 2, wherein On at least a part of the interface between the first positive electrode active material particles and the solid electrolyte and at least a part of the interface between the second positive electrode active material particles and the solid electrolyte, there is a coating film containing an ion conductive material.

4. The positive electrode according to claim 3, wherein When at least one element among boron B, aluminum Al, silicon Si, phosphorus P, titanium Ti, germanium Ge, zirconium Zr, niobium Nb, indium In, tin Sn, hafnium Hf, tantalum Ta, and tungsten W is set as X, and at least one element among oxygen O, sulfur S, fluorine F, chlorine Cl, bromine Br, and iodine I is set as Y, the coating film contains a compound represented by LiXY as the ion conductive material.

5. The positive electrode according to claim 3 or 4, wherein The ion conductive material is LiNbO3.

6. The positive electrode according to any one of claims 1 to 5, wherein A part of the solid electrolyte is in contact with the positive electrode current collector.

7. A solid battery, sequentially comprising the positive electrode according to any one of claims 1 to 6, a solid electrolyte layer, and a negative electrode.

Citation Information

Patent Citations

  • All-solid battery

    JP2014238925A

  • Electrode composite, method for manufacturing electrode composite, positive electrode active material layer, and lithium battery

    JP2017157529A